2023
DOI: 10.3390/polym15030625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Polishing on Physical Properties of an Occlusal Splint Material for Additive Manufacturing under Protection Gas Post-Curing Condition

Abstract: The aim of this study was to evaluate the effect of surface polishing as well as the post-curing atmospheres (air and nitrogen gas) on the physical properties of an occlusal splint material for additive manufacturing. Flexural strength, flexural modulus, Vickers hardness number (VHN), degree of carbon double bond conversion (DC), water sorption (WSP), and water solubility (WSL) were evaluated. Surface polishing significantly affected the evaluated properties. Regardless of the post-curing atmosphere, flexural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Although the superficial layer of the inner surface of the occlusal splint is rarely removed, that of the outer surface is occasionally removed by adjusting the occlusal contact and/or surface polishing. A previous study indicated that superficial layer removal enhanced the mechanical properties, including DC and water solubility, of the PMMA-based materials used in additive-manufactured occlusal splints [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although the superficial layer of the inner surface of the occlusal splint is rarely removed, that of the outer surface is occasionally removed by adjusting the occlusal contact and/or surface polishing. A previous study indicated that superficial layer removal enhanced the mechanical properties, including DC and water solubility, of the PMMA-based materials used in additive-manufactured occlusal splints [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies of nitrogen-saturated post-curing modes suggest improved physical properties on surfaces, it is suggested that these advantageous effects are only restricted to the surface. If the post-cured surface was removed by a polishing procedure, there was no significant difference in microhardness or degree of conversion rate [ 21 ]. This might be obvious, since the nitrogen-saturated atmosphere is only in contact with the surface of the prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently developed post-curing machines decrease the concentration of oxygen in the air by filling the curing chamber with nitrogen, and it has been reported that post-curing in a nitrogen-saturated condition can reduce the contact of oxygen radicals with the surface of 3D-printed resins and therefore improve their mechanical properties [ 14 , 16 , 17 , 18 ]. Also, many studies have demonstrated improvements in the surface characteristics of 3D-printed resins that are post-cured in nitrogen-saturated conditions [ 19 , 20 , 21 ]. However, no studies regarding the optical properties of 3D-printed resins post-cured under nitrogen-saturated conditions, such as color and translucency, have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed post-curing machines decrease the concentration of oxygen in the air by filling the curing chamber with nitrogen, and it has been reported that post-curing in a nitrogensaturated condition can reduce the contact of oxygen radicals with the surface of 3D-printed resins and therefore improve their mechanical properties [14,[16][17][18]. Also, many studies have demonstrated improvements in the surface characteristics of 3D-printed resins that are post-cured in nitrogen-saturated conditions [19][20][21]. However, no studies regarding the optical properties of 3D-printed resins post-cured under nitrogen-saturated conditions, such as color and translucency, have been reported so far.…”
Section: Introductionmentioning
confidence: 99%